Public sector pay policy and private sector wages - Tachibana, Thiago Yudi (2019)
We develop an equilibrium wage posting job search model with a public sector. We investigate the impact of public sector wage policy on labor market outcomes – specifically, the effect on private sector wage setting behavior. The model is tractable: we prove existence and uniqueness of equilibrium and also provide formal comparative statics results. Our motivation stems from the 10 log point increase in the public-private wage gap in Brazil during 2002-2012 – a largely overlooked fact in the discussion of Brazil’ inequality decline. This is still work in progress, and in the empirical implementation we will estimate the model and use it to evaluate the equilibrium impact of this increase in public sector wages.